MENEMPA WIRAUSAHAWAN MUDA DIGITAL: WORKSHOP ENTREPRENEUR BERBASIS PRAKTIK UNTUK PENGUATAN KOMPETENSI DIGITAL MARKETING, DESAIN BRAND, HAK CIPTA, DAN AKUNTANSI SISWA SMK PGRI SUKOHARJO - Nurita Elfani Prasetyaningrum; Ramadhian Agus Triono Sudalyo; Gesang Kristianto Nugrohotomo; Bayu Mukti (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service program aims to enhance digital entrepreneurship competencies among students of SMK PGRI Sukoharjo through an Entrepreneur Workshop covering digital marketing, brand design, copyright literacy, and basic accounting. The workshop was designed to provide both conceptual understanding and hands-on experience, enabling students to develop business ideas creatively and systematically. The implementation methods included interactive lectures, demonstrations, guided practice sessions, and mentoring. Evaluation was carried out using pre-test and post-test assessments to measure the effectiveness of the program. The results demonstrate a significant improvement in students' knowledge and skills, indicated by an increase in the average pre-test score of 58.4 to a post-test score of 83.7, representing a 43.3% improvement. Participants also successfully produced digital content prototypes, basic brand identity designs, and demonstrated understanding of copyright protection and simple financial recording. Furthermore, 87% of students reported that the workshop was highly relevant to their preparation as young entrepreneurs in the digital era. These findings indicate that practice-oriented workshops can substantially strengthen students' entrepreneurial readiness.